Ecosystem Services : Global Issues, Local Practices - Jacobs, Sander; Dendoncker, Nicolas; Keune, Hans (Elsevier Science, 2014)
Ecosystem Services: Global Issues, Local Practices covers scientific input, socioeconomic considerations, and governance issues on ecosystem services. This book provides hands-on transdisciplinary reflections by administrators and sector representatives involved in the ecosystem service community. Ecosystem Services develops shared approaches and scientific methods to achieve knowledge-based sustainable planning and management of ecosystem services. Professionals engaged in ecosystem service implementation have two options: de-emphasize the ecological and socioeconomic.- Resumé vydavatel
Keywords: ekosystémové služby; ecosystem services; elektronické knihy; sborníky; electronic books; papers of several authors